Reforming Individual Income Tax Is the Crucial Factor in Stabilizing the Budgetary System - Povarova Anna Ivanovna (Economic and Social Changes: Facts, Trends, Forecast, 2017)
The reason for writing this article was a statement of the First Deputy Finance Minister Tatyana Nesterenko who claimed that in 2017 the government would run out of money to pay salaries to budgetary sphere employees [3]. Indeed, the reserves accumulated in the fat years are running out. The Government of the Russian Federation finds the following sources to cover the growing budget deficit: first, privatization of the remnants of state property, which will create a momentary effect and will not become a stable channel for filling the treasury; and second, major cuts on spending that on the eve of the electoral cycle can aggravate protest moods of Russians caused by a sharp deterioration of the standard of living. The majority of representatives of the expert and scientific community, including ISEDT RAS employees, consider the urgent need to reform the system for taxation of individual income tax by introducing a progressive tax scale as one of the main solutions to the growing imbalance of the budgetary system. This scale is applied successfully in all the countries of the OECD, G20 and BRICS. The goal of the present paper is to substantiate the need for reformation of individual income tax as a driving force of sustainable mobilization of budget funds. As a hypothesis, an assumption is made concerning the existence of a direct link between the redistribution of income through progressive taxation and an increase in the resource potential of the budgetary system. Research findings presented in the paper confirm that the current mechanisms for taxation of people’s incomes do not correspond to the constitutional principles of equality, social orientation and economic viability. As a result, judging by the most important indicators of socioeconomic development, Russia lags behind developed countries and some comparable developing countries. Excessive income polarization brings to the fore the issue concerning individual income tax modification. The Russian leadership ignores the introduction of progressive taxation of individual income. Meanwhile, according to the most approximate calculations, if incremental taxation rate is applied to the incomes of 77 super-rich Russian businessmen, it will help replenish the budget by 2.2 trillion rubles that will solve the debt crisis issue in Russia’s regions, and in the future – significantly reduce the level of subsidization and dependence on the federal center